1976
DOI: 10.1128/jvi.19.1.228-231.1976
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the tox gene in the prophage of corynebacteriophage beta

Abstract: The orientation of the gene for diphtheria toxin, tox, in the prophage of converting corynebacteriophage beta has been determined. The orientation of tox in prophage and that reported simultaneously by Holmes (1976) for vegetative phage are compatible with the hypothesis that beta phage is inserted into the chromosome of its bacterial host by means of a mechanism similar to that described for lambda phage, and that the phage attachment site lies between the tox and imm genes. The position of three tox mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…Second, the location of ctx also differs from those of other phageassociated toxin genes. Those toxin genes are usually located adjacent to the attP site on the phage genomes (Laird and Groman, 1976;Betley and Mekalanos. 1985;Johnson etai, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the location of ctx also differs from those of other phageassociated toxin genes. Those toxin genes are usually located adjacent to the attP site on the phage genomes (Laird and Groman, 1976;Betley and Mekalanos. 1985;Johnson etai, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic evidence strongly suggests that transcription of tox proceeds toward att (16,18), the precise location of att on the vegetative map was not known. Laird and Groman (16) have presented two possible orientations of imm and tox on the prophage map which suggest that the vegetative gene order between h and h' may be either h' imm tox att h or h' imm att tox h. We have recently probed Southern blots ofEcoRI-digested DNA extracted from lysogenic and nonlysogenic C. diphtheriae with 32P-labeled / DNA and have positioned the att site in the approximate 1-kb region between the EcoRI-1-5 and BamHI-4-9 restriction sites (Michel, Rappuoli, Murphy, and Pappenheimer, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The alleles tox-l, tox-2, tox-30, and tox-45 of the toxin structural gene encode CRMs with molecular weights of 20,000), 26,000, 30,000), and 45,000), respectively (11,29). The orientation of transcription of mRNA from the toxin structural gene is from h toward/i' (11,16). The tox-201 regulatory mutation is expressed in a cisdominant manner with respect to the adjacent toxin structural gene (31).…”
Section: Resultsmentioning
confidence: 99%
“…Previous genetic studies have defined the tox locus of phage /8 (12,15,26), identified the relative positions of several point mutations within the toxin structural gene (11,16), and determined the orientation of transcription of the toxin structural gene (11,16). The present studies were performed to determine the location of the tox-201 regulatory site on the genetic map of phage /3.…”
mentioning
confidence: 99%